Combining Qualitative and Quantitative Methods in Data Analysis - Novalita Fransisca Tungka (Sintuwu Maroso Journal of English Teaching, 2016)
In past days, the educational researchers often dichotomize qualitative and quantitative methods since the characteristics of both methods are different. Nowadays, there is awareness among the researchers to combine these methods due to providing more valid and accurate data for their research. This essay brieflydiscusses the objectives of combining qualitative and quantitative methods in dataanalysis, hence proposes triangulation as the appropriate model of mixed methods to be applied in the research process.Keywords: mixed methods, qualitative, quantitative, triangulation